The Influence of Fiscal Balance Funds and Regional Own-Source Revenues on Regional Expenditures - Witra Maison; Nidia Anggreni Das; Kartilah, Dise Apri (Future Science, 2024)
The purpose of this study is to examine the relationship between regional original income and general allocation funds as well as the spending patterns of regency and municipal administrations in West Sumatra Province from 2018 to 2022. Twenty regencies/cities and West Sumatra Province were selected for the sample using a comprehensive sampling technique within the allotted period. A t-test result of 7.788 and a significance level of 0.000 demonstrate that the General Allocation Fund does, in fact, have an effect on Regional Expenditures. There is a discrepancy between the calculated t-value (7.788) and the t-table value (1.987), which means that the significance value (0.000) is less than 0.05. There is no statistically significant relationship between regional original income and regional expenditures, as shown by the calculated t-test result of 1.389 and a significance value of 0.168. The comparison reveals that the calculated t-value (1.389) is lower than the t-table value (1.987), and that the significance value (0.168) is more than 0.05. However, Regional Expenditures are affected by both the General Allocation Fund and Regional Original Income, as shown by the F-test result of 51.233. This number is much lower than the 0.05 cutoff and higher than the 3.10 F-table value at the 0.000 level of significance.